Cholemic Nephropathy: Hyperbilirubinemia and its Impact on Renal Function - Jonathan S Chávez-Iñiguez; Alejandra Meza-Ríos; Arturo Santos-Garcia; Guillermo García-García; Juan Armendáriz-Borunda (Journal of Renal and Hepatic Disorders)
Cholemic nephropathy represents a spectrum of renal injury, from proximal tubulopathy to intrarenal bile cast formation, found in patients with severe liver dysfunction. It is caused by hyperbilirubinemia, usually in jaundiced patients. Acute kidney injury is one of the most important complications in patients with end-stage liver disease. The relationship between liver disease and renal impairment, especially the effect of hyperbilirubinemia on renal tissue and renal function, has not been fully elucidated. These considerations deem necessary for nephrologists, when performing a clinical evaluation of patients with liver diseases, for the implementation of an integrated medical approach. This review focuses on the current knowledge on cholemic nephropathy with emphasis on the role of hyperbilirubinemia on renal impairment. The treatment strategies and outcome are also discussed.